Pediatric Nonrhabdomyosarcoma Soft Tissue Sarcomas - Sheri L. Spunt; Stephen X. Skapek; Cheryl M. Coffin (2008)
Abstract Learning Objectives After completing this course, the reader will be able to: Evaluate the clinical features of NRSTS in pediatric patients.Identify the factors that influence the selection of treatment and the clinical outcomes of pediatric patients with NRSTS.Select an appropriate treatment strategy for pediatric patients with NRSTS. CME This article is available for continuing medical education credit at CME.TheOncologist.com The nonrhabdomyosarcoma soft tissue sarcomas (NRSTSs) are a heterogeneous group of mesenchymal cell neoplasms that account for about 4% of childhood cancers. Because each histologic subtype of NRSTS is rare, they have been poorly studied and little is known about their biology, natural history, or optimal treatment. Data from adults with soft tissue sarcomas provide some helpful insight, but adult and childhood NRSTSs differ considerably in the distribution of their histologic subtypes, and certain entities are known to behave differently in young children. The greater risks posed to children by treatment, particularly by radiotherapy, also must be considered in treatment planning for children. This article summarizes what is known to date about childhood NRSTS, including the epidemiology, pathogenesis, and clinical approach to diagnosis and treatment of these tumors.